HPTLC simultaneous quantification of triterpene acids for quality control of Plantago major L. and evaluation of their cytotoxic and antioxidant activities - Piyaviriyakul, S.; Siripong, P.; Vallisuta, O.
A validated high performance thin-layer chromatography (HPTLC)method was developed for simultaneous determination of ursolic acid (UA)and oleanolic acid (OA)contents in Plantago major which were collected from several plantation areas in Indonesia. The cytotoxic effect against two cancer cell lines, SiHa and Hep G2, and antioxidant activity were evaluated using the MTT and DPPH-radical scavenging assay, respectively. The test samples included various extracts of P. major from different plant parts using methanol and water as extracting solvents and pure compounds derived from this plant. The results showed that both plant parts and extracting solvents affected the chemical contents and their biological activities. The contents of UA and OA varied according to the organs and provenances of plant. The highest content of UA (0.22-0.48percent dry weight)and OA (0.17-0.33percent dry weight)were found in the methanol extract of seed. This extract also exhibited the highest cytotoxic activity (IC50 value: 174.42-246.38 ?g/ml), whereas the strongest free radical scavenging activity was obtained from the leaf methanol extract (IC50 value: 263.57 ?g/ml). The developed HPTLC method can be used for routine analysis and standardization of P. major crude drugs, extracts, and/or finished products using UA and OA as appropriate markers for anticancer products.
Keywords: CYTOTOXIC; ANTIOXIDANT; URSOLIC ACID; OLEANOLIC ACID; HPTLC; SIMULTANEOUS ANALYSIS